Modernity and the Spanish-American Short Story (ALPHA. Journal of Arts, Literature and Philosophy, 2002)
This essay studies the dynamics of the modern Spanish-American short story from works published in the last two decades of the 19th century until the close of the 20th century. This interrelated approach to the development of Spanish-American short story is based on a dialogical view of modernity. Modernity is a concept understood as a sensibility,  writing and a new vision which made possible the peculiar strength and sustained productivity of the Latin American short story. Instead of studying literary history in self-contained styles, fractional tendencies and generations, I look at the globalization of its aesthetic components, thus seeking a new,  more comprehensive reading of the Spanish American short story, one that may explain the interconnectedness of a writing renewed by the intertextual dimension of change.